Ground State and Magnetostatic Properties of a Dipole System Arranged in Two-Dimensional Lattice - Bolcal, Ertuğrul Cem; Dimitrov, Ventsislav; Aktaş, Bekir; Aslan, Muhammed Hasan; Bozkurt, A. (Polish Acad Sciences Inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2012)
A system of nano sized modomain ferromagnetic particle arranged in two-dimensional lattice is theoretically investigated. The basic aim of the investigation is to find the ground state of these types of models where the interaction is long-ranged and anisotropic. The numerical calculations show that for some lattices there is a number of degenerated states near the zero temperature. The ground state of these systems is basically of a complicated antiferromagnetic type.
Keywords: interacting particles; models; etkileşen parçacıklar; modeller